(untitled) (Analele Universității București. Limba și literatură română, 2024)
Salvatore Attardo is one of the most important scholars for linguistic approach to humour. His books and articles have been highly influential since the early 1990s: “Script Theory revis(it)ed: Joke similarity and joke representation model” (1991, with Victor Raskin), Linguistic Theories of Humor (1994), Humorous Texts: A Semantic and Pragmatic Analysis (2001), to mention only a few. He also edited The Encyclopedia of Humor Studies (2014) and The Routledge Handbook of Language and Humor (2017). His 2020 book, The Linguistics of Humor. An introduction, is written with a pedagogical aim (as claimed by the author in the Preface), for both students and scholars interested in humour but lacking the linguistic background.